Ratings of pain and activity limitation on the visual analogue scale and global impression of change in multimodal rehabilitation of back pain – analyses at group and individual level. Issue 22 (22nd October 2016) - Elfving, B.; Lund, I.; C, Lüning Bergsten; Boström, C.
Abstract: Purpose: To evaluate changes in pain intensity and activity limitation, at group and individual levels, and their associations with the global impression of change after multimodal rehabilitation in patients with back pain. Method: Patients with long-term back pain ( n = 282) participated in a 4-week programme with a follow-up after 6 months. Visual analogue scales (VAS) were used to rate pain intensity and activity limitation. Global impression of change (GIC) was rated on a 7-category scale. The sign test, the Svensson method and the Spearman rank correlation were used for analyses. Results: Significantly lower ratings in pain and activity limitation at follow-up were found at group level. However, a large individual variability was found by the Svensson method. The correlations between GIC and changes in pain and activity limitation were r s = 0.49 and r s = 0.50, respectively. A rated GIC of at least "much better" on group level showed changes of ≥20 mm on the VAS. Conclusions: At group level, lower VAS ratings were found in patients with back pain. However, a large individual variability in pain and activity limitation was also found resulting in low to moderate associations between GIC and the change in VAS ratings. The large individual variability might be due to the impreciseness in the ratings on the VAS. We have presented a critical discussion of statistical methods in connection with the VAS. Implications for Rehabilitation: The use of VAS as a rating instrument may be questioned, especially for perceived pain intensity which is a too complex experience to be rated on a line without any visible categories. Single ratings of pain intensity should preferably be complemented with the ratings of activity limitation in patients with long-term back pain. Global impression of change is a suggested inclusive rating after rehabilitation. The improvement desired by the patient should preferably be determined before rehabilitation.